2020
DOI: 10.1002/14651858.cd013051.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Topical antibiotics for chronic suppurative otitis media

Abstract: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of topical antibiotics for people with chronic suppurative otitis media (CSOM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 128 publications
0
37
0
3
Order By: Relevance
“…Since drug-loaded slabs F6-0.5 and H6-0.5 demonstrated to be highly efficient against both Gram-negative and Gram-positive bacteria, only F6-0.5 and H6-0.5 were chosen for a detailed monitoring of the drug release profiles to avoid waste of drug and concerns on toxicity. This information should allow the prediction for how long the hearing aids could continue delivering the drugs, keeping in mind that otitis requires one or two weeks pharmacological treatment [42]. Ciprofloxacin hydrochloride is a hydrophilic antimicrobial agent (solubility 170 µg/mL in PBS; log P -0.94) [70], while fluocinolone acetonide is a relatively hydrophobic corticosteroid (solubility 17 µg/mL in PBS; log P 2.24) [71].…”
Section: Drug Release Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since drug-loaded slabs F6-0.5 and H6-0.5 demonstrated to be highly efficient against both Gram-negative and Gram-positive bacteria, only F6-0.5 and H6-0.5 were chosen for a detailed monitoring of the drug release profiles to avoid waste of drug and concerns on toxicity. This information should allow the prediction for how long the hearing aids could continue delivering the drugs, keeping in mind that otitis requires one or two weeks pharmacological treatment [42]. Ciprofloxacin hydrochloride is a hydrophilic antimicrobial agent (solubility 170 µg/mL in PBS; log P -0.94) [70], while fluocinolone acetonide is a relatively hydrophobic corticosteroid (solubility 17 µg/mL in PBS; log P 2.24) [71].…”
Section: Drug Release Studiesmentioning
confidence: 99%
“…In the case of ear infections, topical antibiotics are better than aural toilet (ear cleaning using dry mopping or irrigation) alone, and systemic or topical fluoroquinolones (e.g. ciprofloxacin, ofloxacin) are more effective than other types of antibiotics [42,43]. It has also been reported that the use of ciprofloxacin in combination with fluocinolone acetonide is more effective than treatment with each drug individually for acute otitis media with tympanostomy tubes (AOMT) in children and is safe and well tolerated [44,45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 When otorrhea persists for 2 weeks or longer with a nonintact tympanic membrane (tube or perforation), additional topical antibiotics, with or without concurrent oral antibiotic, appear effective, but the quality and consistency of supporting evidence is low. 37 Expert insight and opinion. Effective management of recurrent or persistent TTO begins with identifying the likely cause, based on the laterality and temporal pattern ( Table 5).…”
Section: What Is the Best Way To Manage A Child With Recurrent Or Permentioning
confidence: 99%
“…[19] mencionan que la administración de ciprofloxacino por vía oral asociado a la administración por vía tópica no aportó beneficio alguno frente a las vías de administración exclusivamente tópicas, con respecto a esto Brennan y Cols. [20] expresan que existe mucha incertidumbre acerca de si los antibióticos tópicos mejoran o no la resolución de la secreción del oído en los pacientes con otitis media supurativa crónica. Pensamos que desde el punto de vista clínico, el abordaje terapéutico de las patologías ambulatorias del oído, no solo debe enfocarse al tratamiento sintomatológico sino que debe orientarse a obtener la curación completa del proceso causal, ya que como se observó en nuestro estudio la antibioterapia prolongada no es del todo eficaz para evitar las frecuentes recidivas y complicaciones, por lo que expresamos que el uso significativo de antibióticos orales, más allá de la terapia tópica, podría tener implicaciones en términos de costo, aparición de resistencia microbiana, riesgo de efectos secundarios y mayor probabilidad de incumplimiento terapéutico por parte del paciente, con respecto a esto Migirov y cols.…”
Section: Materials Y Métodounclassified